Non-Linear Inversion Method to Derive Bathymetry from Video Images - Zikra, Muhammad; Hashimoto, Noriaki; Suzuki, Kojiro; Plant, Nathaniel G. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This study investigates the capabilities of optical remote sensing to monitor bathymetry in nearshore area using video images. The technique is designed to extract wave number components based on variation of intensity of brightness at each pixel in the images using cross-spectral correlation approach. This approach is based on pixel array analysis that utilizes a nonlinear inverse method 'Levenberg-Marquardt’. The technique is applied to the data collected at Hasaki beach in Japan from August to December 2006. The results indicate that the cross-spectral correlation approach have the capability to derive wave number estimate from time series data of video images with small rms errors (0.0342-0.0421). Also, the estimate of nearshore bathymetry is proved reasonable accurate near shoreline and breaking area where the differences between estimated and survey water depth are less than 10-30 cm.